2021
DOI: 10.1021/acs.organomet.0c00782
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Metal-Catalyzed Polyethylene Depolymerization: [(Phen)Pd(X)]+ (X = H and CH3) Catalyze the Decomposition of Hexane into a Mixture of Alkenes via a Complex Reaction Network

Abstract: The ternary Pd complexes [(phen)­Pd­(H)]+ (1-Pd) and [(phen)­Pd­(CH3)]+ (5-Pd) (where phen = 1,10-phenanthroline) both react with hexane in a linear ion trap mass spectrometer, forming the C–H activation product [(phen)­Pd­(C6H11)]+ (3-Pd) and releasing H2 and CH4, respectively. Density functional theory (DFT) calculations agree well with the experiments in predicting low barriers for these reactions proceeding via a metathesis mechanism. Species 3-Pd undergoes extensive fragmentation, or “cracking”, of the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 75 publications
(60 reference statements)
1
13
0
Order By: Relevance
“…Similar to the work of the Schwarz group on alkane dehydrogenation using related Pt complexes, we found that these complexes can catalyze dehydrogenation of ethane (Scheme , left cycle) . We also found that for hexane, cracking of the chain via C–C bond activation reactions can compete with dehydrogenation; Ni and Pd were found to favor cracking (Scheme , right cycle), while Pt favored dehydrogenation . Here, we explore the activation of cyclohexane by [(phen)­M­(X)] + complexes.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Similar to the work of the Schwarz group on alkane dehydrogenation using related Pt complexes, we found that these complexes can catalyze dehydrogenation of ethane (Scheme , left cycle) . We also found that for hexane, cracking of the chain via C–C bond activation reactions can compete with dehydrogenation; Ni and Pd were found to favor cracking (Scheme , right cycle), while Pt favored dehydrogenation . Here, we explore the activation of cyclohexane by [(phen)­M­(X)] + complexes.…”
Section: Introductionsupporting
confidence: 59%
“…23 We also found that for hexane, cracking of the chain via C−C bond activation reactions can compete with dehydrogenation; Ni and Pd were found to favor cracking (Scheme 1, right cycle), while Pt favored dehydrogenation. 24 Here, we explore the activation of cyclohexane by [(phen)M(X)] + complexes. Since the C−H bond dissociation energy in cyclohexane is similar to those of the 2-and 3positions in hexane, it is highly likely that [(phen)M(X)] + will activate C−H bonds in cyclohexane.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unimolecular reaction of the product ion was subjected to CID (Figure S2). Multiple fragmentation pathways were observed involving deinsertion of n -pentylallene; loss of phenanthroline; loss of the allyl group; and cleavage of the aliphatic chain . Unlike the phenyl complex 2a , the ortho -dimethoxy-substituted aryl-palladium complex 2b has much lower reactivity with phenylallene, and no reaction with n -pentylallene was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Chamas, et al [104] described benchmarks for decay rates of usual plastics that will assist in prioritizing future study attempts on chemical decay to close the loop. Parker, et al [105] investigated the depolymerization of ethylene with palladium catalysts to comprehend techniques to remediation of polyolefins. Liu, et al [106] focused on the recuperation of lithium from spent batteries employing an acid-free mechanochemical method, which uses salt and sodium carbonate as the sole reagents.…”
Section: Closing the Loopmentioning
confidence: 99%